Culpabilidade no direito penal: a ilusão do poder agir de outro modo a partir do problema do livre-arbítrio - Varjão, Alan Jefferson Santos (2014)
We have here a theoretical research that intends to question the concept of culpability, in other words, the idea of being able to act otherwise considering the problem of free will. We argue that the concept of culpability is legitimized by a libertarian sense of free will in the common sense that has no empirical basis. Thus, given the impossibility of proving the existence of free will, we affirm that the criminal law cannot justify punishment on desert. Despite the compatibilist appearance, the idea of being able to do otherwise is supported implicitly by a libertarian point of view. In other words, the judgment of disapproval is justified by an untenable notion of freedom. The idea is to demonstrate that the way people see free will is an illusion because the assumptions that sustain it are false. In support, we use arguments of some philosophers and discoveries of neuroscience. From them, we demonstrated that the only way out of culpability is the normative presumption based on an a priori concept of average man. Besides false free will, the culpability brings a sense of moral realism that cannot be sustained in the face of some discoveries of neuroscience. In the background, we showed the evolution of criminal law as a systematic construction and the role played by culpability in the criminal dogmatic system. With the denial of the normative concept, we analyzed the functionalism of Claus Roxin and Gunther Jakobs, and also the theory of utilitarianism by deterrence.